2006
DOI: 10.1108/00070700610644906
|View full text |Cite
|
Sign up to set email alerts
|

The role of food quality certification on consumers' food choices

Abstract: PurposeThe purpose of this paper is to examine consumer attitudes and behavior towards organic products and products produced under the system of integrated management (SIM) and to compare the socioeconomic characteristics and attitudes that affect consumers' willingness to pay (WTP) a premium for these two different certification systems.Design/methodology/approachThe study is based on cross‐sectional data collected through a questionnaire survey. Respondents' attitudes towards the organic and SIM certificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
143
1
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(174 citation statements)
references
References 18 publications
12
143
1
18
Order By: Relevance
“…Marital status is significant but negatively related to WTP. Other studies have not found a consistent relationship between marital status and WTP or actual amounts paid for organic produce (positive: Botonaki et al 2006;insignificant: Groff et al 1993;negative: Lin et al 2008). This unexpected finding could be attributable to the additional financial commitments married households have (e.g., children or elders) and reduced disposable income these households have to pay a premium for organic foods after controlling for household income.…”
Section: Organic Modelmentioning
confidence: 99%
“…Marital status is significant but negatively related to WTP. Other studies have not found a consistent relationship between marital status and WTP or actual amounts paid for organic produce (positive: Botonaki et al 2006;insignificant: Groff et al 1993;negative: Lin et al 2008). This unexpected finding could be attributable to the additional financial commitments married households have (e.g., children or elders) and reduced disposable income these households have to pay a premium for organic foods after controlling for household income.…”
Section: Organic Modelmentioning
confidence: 99%
“…Previous research suggests that personal health concerns may drive consumers' attitudes toward organic food (Botonaki, Polymeros, Tsakiridou, & Mattas, 2006;Chryssohoidis & Krystallis, 2005;Harper & Makatouni, 2002;Kareklas, Carlson, & Muehling, 2014;Magnusson et al, 2003;Makatouni, 2002;Padel & Foster, 2005) MOTIVES UNDERLYING ORGANIC FOOD CONSUMPTION IN TURKEY 335 and intention to purchase organic food (Kareklas et al, 2014;Schifferstein & Oude Ophuis, 1998;Soler, Gil, & Sanchez, 2002). Individuals' perception that organic food is healthier with greater nutritional value compared to conventional food, and produced naturally without using harmful chemicals results in positive attitudes towards organic food (Kareklas et al, 2014;Ott, 1990;Pino, Peluso, & Guido, 2012;Squires, Juric, & Cornwell, 2001;Wandel & Bugge, 1997;Wilkins & Hillers, 1994).…”
Section: Organic Food Consumption Motivesmentioning
confidence: 99%
“…Briefly, therefore, we would first mention those authors who have analyzed differences between organic and conventional food consumers. A number of studies have tried to analyze the drivers of organic food consumption (Jolly et al, 1989;Beharrell and MacFie, 1991;Grunert and Juhl, 1995;Wandel and Bugge, 1997;Lohr and Krissoff, 2001;Magnusson et al, 2003;Yiridoe et al, 2005;Botonaki et al, 2006;De Magistris and Gracia, 2008;Tsakiridou et al, 2008;Chen, 2009, among others). Then there is another group examining willingness to pay a premium for organic over conventional food products (Fotopoulos and Krystallis, 2002;Krystallis and Cryssohoidis, 2005;Botonaki et al, 2006); organic food consumers' sociodemographic features (Tsakiridou et al, 2008;Wier et al, 2008) and their purchase behaviour (Ritcher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%